A Sustained Partnership between a Haitian Children's Hospital and North American Academic Medical Centers - Michael P. Koster; Jackson H. Williams; Jacqueline Gautier; Renee Alce; Bernard E. Trappey (Frontiers Media S.A., 2017)
Global health initiatives from academic medical centers have rapidly proliferated over the last decade. This paper endeavors to describe our 5-year experience as an academic medical collaborative supporting healthcare delivery, medical training, and research at Hôpital Saint Damien-Nos Petits Frères et Soeurs, the only freestanding children's hospital in Haiti. Descriptions of the history and current activities of our academic medical collaborative, its partnership and communication structure, its evolution to fill the expressed needs of our host site, its funding mechanisms, and its challenges and opportunities for the future are included.